2021
DOI: 10.1371/journal.pone.0255917
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary tumor embolism: A retrospective study over a 30-year period

Abstract: Background Pulmonary tumor embolism (PTE) is difficult to detect before death, and it is unclear whether the discrepancy between antemortem clinical and postmortem diagnosis improves with the advance of the diagnostic technologies. In this study we determined the incidence of PTE and analyzed the discrepancy between antemortem clinical and postmortem diagnosis. Methods We performed a retrospective autopsy study on patients with the history of malignant solid tumors from 1990 to 2020 and reviewed all the slid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…The most common primary tumors to present with PTE are breast, gastric, hepatocellular, urothelial, esophageal, lung, and pancreatic carcinomas. 4 Unfortunately, PTE is rarely diagnosed ante mortem, and its prevalence in autopsy series of patients with solid tumors ranges between 3% and 26% and is dependent on the institution’s autopsy sampling rate. 3 , 4 Discrepancy between the antemortem clinical diagnosis and the postmortem autopsy diagnosis has not improved substantially over the past 30 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common primary tumors to present with PTE are breast, gastric, hepatocellular, urothelial, esophageal, lung, and pancreatic carcinomas. 4 Unfortunately, PTE is rarely diagnosed ante mortem, and its prevalence in autopsy series of patients with solid tumors ranges between 3% and 26% and is dependent on the institution’s autopsy sampling rate. 3 , 4 Discrepancy between the antemortem clinical diagnosis and the postmortem autopsy diagnosis has not improved substantially over the past 30 years.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 Discrepancy between the antemortem clinical diagnosis and the postmortem autopsy diagnosis has not improved substantially over the past 30 years. 4 …”
Section: Discussionmentioning
confidence: 99%
“…A very recent study intended to determine the discrepancies between the antemortem diagnosis and autopsy results. The conclusion was that despite a significant improvement in radiological technologies over the past 30 years, the disparity between antemortem diagnosis and autopsy does not differ significantly [ 95 ].…”
Section: Tumor Embolismmentioning
confidence: 99%
“…It was identified that all the patients had advanced carcinoma with distant metastases, and metastatic liver carcinoma was observed in 14 patients. It was also reported that breast carcinoma was among the most common primary malignancy overall [ 5 ]. This case study includes an elderly female patient with breast carcinoma with secondary metastasis to the liver and pulmonary embolus tumor.…”
Section: Introductionmentioning
confidence: 99%